TINDAK TUTUR ILOKUSI DALAM NOVEL KITAB CINYA YUSUF ZULAIKHA KARYA TAUFIQURRAHMAN AL-AZIZY - Hasbullah Ridwan, Muhammad (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2023)
A speech act is an action displayed through speech. This means that something like this contains an assumption that the speech we utter is not actually empty speech without any action in it, or empty of the context that is happening. This research aims to determine the form and meaning of illocutionary speech acts in the novel Buku Cinta Yusuf Zulaikha. This research uses a qualitative descriptive method aimed at describing in detail the illocutionary speech acts and their meanings in the novel Buku Cinta Yusuf Zulaikha. Research data collection techniques use listening techniques and note-taking techniques, data analysis techniques in this research include planning, starting data collection, basic data collection, closing data collection, and completing. The results of this research are that there are 23 illocutionary speech acts, consisting of Representative, Directive, Expressive and Declaration.